Networked Learning in Applied Science Education - Pauschenwein, Jutta; Koubek, Anni (Proceedings of the International Conference on Networked Learning, 2000)
In addition to traditional universities. within the last 5 years a number of applied science tertiary education programs ("Fachhochschulen") have been developed in Austria. The reason for this development was to install programs which are targeted co specific industrial needs and provide shorter, more targeted education. The courses are industry-oriented, compact and integrate theoretical knowledge with practical know-how. The didactical framework differs quite substantially from traditional university courses. The cooperation with industry accompanies the student through the whole study course. The majority of lecturers are working in industry and teach only part time. Projects in cooperation with industry, often including several subjects, arc posed in a group oriented approach, starting from the very first year. The complexity and professionality of such projects increases during the study time. Also each student works at least half a year with a company. This practical work is an integrated part of the courses and followed up by the teaching staff. Currently the FH Joanneum offers 9 study courses, all in very specialised, technologically oriented fields, such as automotive engineering, industrial design or construction planing and management.